2019
DOI: 10.3390/en12214152
|View full text |Cite
|
Sign up to set email alerts
|

A Research on Driving Factors of Carbon Emissions of Road Transportation Industry in Six Asia-Pacific Countries Based on the LMDI Decomposition Method

Abstract: The transportation industry is the second largest industry of carbon emissions in the world, and the road transportation industry accounts for a large proportion of this in the global transportation industry. The carbon emissions of the road transportation industry in six Asia-Pacific countries (Australia, Canada, China, India, Russia, and the United States) accounts for more than 50% of this in the global transportation industry. Therefore, it is of great significance to study driving factors of carbon emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Then, the expressions of each factor, which influences on carbon emissions, are respectively Equations (5)- (9). Similarly with those in reference [34], they are used for the detailed derivation process.…”
Section: Logarithmic Mean Divisia Index (Lmdi) Decomposition Methods Bmentioning
confidence: 99%
“…Then, the expressions of each factor, which influences on carbon emissions, are respectively Equations (5)- (9). Similarly with those in reference [34], they are used for the detailed derivation process.…”
Section: Logarithmic Mean Divisia Index (Lmdi) Decomposition Methods Bmentioning
confidence: 99%
“…Therefore, in this article, the CO 2 emissions stemming from fossil fuel combustion per unit GDP is used to characterize the level of technological progress in the transportation industry (Li et al, 2011). In addition, because CO 2 emissions from road transportation account for the highest proportion of the transportation industry, representing more than 70% (Zhu and Du, 2019), and considering the availability of data, we use road transport turnover to reflect the intensity of transportation activity in each region.…”
Section: Spatial Econometric Modelmentioning
confidence: 99%
“…Zhu and Du ( 2019 ) analyzed the driving factors of CO 2 emissions of road transportation in Australia, Canada, China, India, Russia, and the USA for the period of 1990–2016. The empirical results indicated that carbon emissions of road transportation had a dramatic increase since 1990.…”
Section: Literature Reviewmentioning
confidence: 99%